The Effect of a Deep Learning–Based Multisensory Approach on Primary School Students’ Counting Skills: A literature review - Merlia, Rachmi Suni; Suryandari, Kartika Chysti; Chumdari, Chumdari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
Early mathematics learning is essential for developing elementary students’ numeracy skills, yet rote-based instruction often limits conceptual understanding. Therefore, meaningful and active approaches such as multisensory learning within a deep learning framework are needed. This study aims to examine multisensory approaches in supporting deep learning-oriented early mathematics instruction through a narrative literature review of relevant sources published in the last ten years. Data were analyzed using thematic synthesis focusing on theoretical foundations, implementation strategies, and empirical findings. The results show that multisensory approaches enhance conceptual understanding, student engagement, and overall learning quality, while aligning with deep learning principles that emphasize meaningful and joyful learning. However, studies explicitly integrating both approaches in early mathematics remain limited. Thus, further development of integrative instructional models is recommended to support meaningful and sustainable mathematics learning.